NEW GENERATION ELECTRIC MACHINES (E Conference Zone, 2022)
The prospects for the development of electrical machines are inextricably linked with the prospects for the creation of new power supply systems and electric wires. Sources of electrical energy, both direct and alternating current, can be developed in several directions.